Maternal and newborn health priority setting partnership in rural Uganda in association with the James Lind Alliance: a study protocol - James Ditai; Monicah Nakyazze; Deborah Andrinar Namutebi; Proscovia Auma; Martin Chebet; Cynthia Nalumansi; Grace Martha Nabulo; Kenneth Mugabe; Toto Anne Gronlund; Anthony Mbonye; Andrew D. Weeks (Research Involvement and Engagement, 2020)
Abstract Background Maternal and newborn deaths and ill health are relatively common in low income countries, but can adequately be addressed through locally, collaboratively designed, and responsive research. This has the potential to enable the affected women, their families and health workers themselves to explore ‘why maternal and newborn adverse outcomes continue to occur. The objectives of the study include; 1. To work with seldom heard groups of mothers, their families, and health workers to identify unanswered research questions for maternal and newborn health in villages and health facilities in rural Uganda 2. To establish locally responsive research questions for maternal and newborn health that could be prioritised together with the public in Uganda 3. To support the case for locally responsive research in maternal and newborn health by the ministry of health, academic researchers and funding bodies in Uganda. Methods The present study will follow the James Lind Alliance (JLA) Priority Setting Partnership (PSP) methodology. The project was initiated by an academic research group and will be managed by a research team at the Sanyu Africa Research Institute on a day to day basis. A steering group with a separate lay mothers’ group and partners’ group (individuals or organisations with interest in maternal and newborn health) will be recruited. The PSP will be initiated by launch meetings, then a face-to-face initial survey for the collection of raw unanswered questions; followed by data collation. A face-to-face interim prioritisation survey will then be performed to choose questions before the three separate final prioritisation workshops. The PSP will involve many participants from an illiterate, non-internet population in rural eastern Uganda, but all with an interest in strategies to avert maternal and newborn deaths or morbidities in rural eastern Uganda. This includes local rural women, their families, health and social workers, and relevant local groups or organisations. We will generate a top 10 list of maternal and newborn health research priorities from a group with no prior experience in setting a research agenda in rural eastern Uganda. Discussion The current protocol elaborates the JLA methods for application with a new topic and in a new setting translating the JLA principles not just into the local language, but into a rural, vulnerable, illiterate, and non-internet population in Uganda. The face-to-face human interaction is powerful in eliciting what exactly matters to individuals in this particular context as opposed to online surveys. This will be the first time that mothers and lay public with current or previous experience of maternal or neonatal adverse outcomes will have the opportunity to identify and prioritise research questions that matter to them in Uganda. We will be able to compare how the public would prioritise maternal health research questions over newborn health in this setting.